2023
DOI: 10.2166/wcc.2023.372
|View full text |Cite
|
Sign up to set email alerts
|

Filling streamflow data gaps through the construction of rating curves in the Lake Tana sub-basin, Nile basin

Abstract: In recent decades, streamflow data remain inaccessible for most river gauges in Ethiopia due to a lack of updated stage–discharge relationships, also called rating curves. In this study, researchers and hydrologic technicians collaborated to fill the recent streamflow data gaps at three gauging stations in the Lake Tana sub-basin of the Nile River. We conducted extensive field campaigns to improve the coverage of stage–discharge measurements for rating curve development. We evaluated the rating curve uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As a result, recent data collection is relying on individual research project activities [29,30]. For instance, Haile et al [31] and Taye et al [32] demonstrated how reversing the unavailability of streamflow data in the Lake Tana sub-basin of Ethiopia is possible through supporting data providers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recent data collection is relying on individual research project activities [29,30]. For instance, Haile et al [31] and Taye et al [32] demonstrated how reversing the unavailability of streamflow data in the Lake Tana sub-basin of Ethiopia is possible through supporting data providers.…”
Section: Introductionmentioning
confidence: 99%